Case Study: Factors Causing the High Referral Ratio of BPJS Outpatients at the Mataram Police Primary Clinic in 2025 - Ida Ayu Swathi Antari; Sastrawan Sastrawan; Lalu Abdul Khalik (Jurnal Penelitian Pendidikan IPA, 2026)
The high referral ratio of BPJS outpatients at the Mataram Police Department's Primary Clinic in 2024 is a serious problem because it exceeds established standards, potentially leading to service inefficiencies. This study aims to analyze the causes of this high referral ratio through a review of the structure, process, and outcome aspects, as well as the contextual conditions at the Mataram Police Department's Primary Clinic. The research method used was a qualitative case study design. Data collection was conducted through in-depth interviews with key informants and supporting staff, observation, and document review related to the 2024 referral data. The results showed that, in terms of structure, the main causes of referrals were limited medical infrastructure, inadequate laboratory facilities, and the limited availability of certain medications. In terms of process, it was found that lack of compliance with Standard Operating Procedures (SOPs) and the strong desire of patients to be referred directly to hospitals were driving factors. In terms of outcome, a high rate of non-specialist referrals was still found. Contextual conditions, such as the clinic's position as a National Police health facility, also influenced referral patterns related to internal coordination. In conclusion, the high referral rate at the Mataram Police Department's Primary Clinic in 2024 was due to limited physical resources (structure) and high patient demand (process). It is recommended that primary healthcare facility standards be met and patient education on the tiered referral system strengthened to reduce referral rates